Implementasi Kegiatan Kaligrafi terhadap Nilai-nilai Edukasi Pada Siswa MTs Nur Ibrahimy Rantau Prapat - Fadira, Ayu; Syahputra, Jailani; Syafriyeti, Rahmi (MODELING: Jurnal Program Studi PGMI, 2024)
This study examines the implementation of calligraphy activities on educational values ??in students of MTS Nur Ibrahimy Rantau Prapat. Calligraphy in Islam is not only an expression of art, but also a medium of education and character building. This study uses a descriptive qualitative approach. Data collection techniques are observation, interview, and documentation techniques. The validity of the data in this study uses triangulation techniques. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of calligraphy activities is carried out routinely as part of the madrasah's extracurricular activities with the support of facilities and guidance from experienced teachers. The educational values ??that develop through this activity include spiritual values, motor skills, discipline, patience, creativity, and appreciation for Islamic cultural heritage. The impact of calligraphy activities is seen in increasing students' spirituality, character development, concentration skills, and aesthetic sense. This study concludes that calligraphy is an effective means of forming character and Islamic values ??in students, not only developing beautiful writing skills but also instilling comprehensive educational values. It is recommended that this activity continue to be developed with special training for teachers and the provision of more adequate media. Abstrak Penelitian ini mengkaji implementasi kegiatan kaligrafi terhadap nilai-nilai edukasi pada siswa MTS Nur Ibrahimy Rantau Prapat. Kaligrafi dalam Islam tidak hanya sebagai ekspresi seni, tetapi juga media pendidikan dan pembentukan karakter. Penelitian ini Menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data teknik observasi, wawancara, dan dokumentasi. Validitas data dalam penelitian ini menggunakan teknik triangulasi. Teknik analisis data dalam penelitian ini meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi kegiatan kaligrafi dilaksanakan secara rutin sebagai bagian dari ekstrakurikuler madrasah dengan dukungan fasilitas dan bimbingan guru yang berpengalaman. Nilai-nilai edukasi yang berkembang melalui kegiatan ini mencakup nilai spiritual, keterampilan motorik, kedisiplinan, kesabaran, kreativitas, dan penghargaan terhadap warisan budaya Islam. Dampak kegiatan kaligrafi terlihat pada peningkatan spiritualitas siswa, perkembangan karakter, kemampuan konsentrasi, dan rasa estetika. Penelitian ini menyimpulkan bahwa kaligrafi merupakan sarana efektif dalam membentuk karakter dan nilai-nilai Islami pada siswa, tidak hanya mengembangkan keterampilan menulis indah tetapi juga menanamkan nilai-nilai pendidikan yang komprehensif. Disarankan agar kegiatan ini terus dikembangkan dengan pelatihan khusus bagi guru dan penyediaan media yang lebih memadai.